Kajian Karakteristik Jam Gadang Sebagai Bangunan Ikonik di Kota Bukit Tinggi - Alparuki, Widi; Mirsa, Rinaldi; Saputra, Eri (Jurnal Rekayasa Teknik dan Teknologi, 2025)
Bukittinggi is a city in West Sumatra that has high historical value and has iconic buildings, one of which is Jam Gadang as the pride of the community so that it must be preserved. The research aims to find out the characteristics of the building and the elements that influence it. The method uses descriptive qualitative by conducting observations, surveys, interviews, and documentation. The results of the research are seen from the facade elements and composition of the Jam Gadang facade. Based on the analysis of Jam Gadang facade in terms of facade elements and facade composition. In terms of facade elements, Jam Gadang has a strong cultural character with a bagonjong roof shape and typical Minangkabau cultural ornaments from nature and plant motifs while the overall wall of Jam Gadang looks plain with a dominant white colour that gives a neutral feel to the building. The building door is a double door with a single window and a triangular gevel shape, railing with a small block and circle shape and the absence of columns on the building facade. While the composition of the Jam Gadang facade has a formal and slightly monotonous character with symmetrical balance, static rhythm, vertical rectangular geometry, the proportion of the building height is longer than the building height, and has a dominance of discordant contrast.